Analisis Faktor Administrasi Dan Pelayanan Pada Kejadian Pending Klaim BPJS Kesehatan Rawat Jalan Dalam Perspektif Manajemen Klaim Rumah Sakit - Nina Narjati Soejoto (Journal of Innovation Research and Knowledge, 2026)
Pending claims in the National Health Insurance (Jaminan Kesehatan Nasional/JKN) program administered by BPJS Kesehatan remain one of the challenges in hospital claims management, as they can cause delays in the reimbursement process for healthcare services and affect hospital financial management. The occurrence of pending claims indicates challenges in administrative procedures, the accuracy of service documentation, and coordination among the units involved in the claim submission process. This study aims to analyze administrative and service-related factors associated with pending outpatient claims submitted to BPJS Kesehatan as an effort to improve hospital claims management. This study employed a descriptive quantitative method with a retrospective approach using secondary data consisting of 2,158 outpatient BPJS Kesehatan claim records. Data were analyzed using frequency distributions and percentages based on INA-CBG codes, claim submission amounts, and the reasons for pending claims. The results showed that pending claims occurred due to various administrative and service-related issues, including repeated claims for chronic medications, hemodialysis services, internal consultations, and discrepancies in the claim verification process. The findings indicate that claim administration processes, the accuracy of service documentation, and inter-unit coordination are important aspects that need to be addressed in managing BPJS Kesehatan claims in hospitals. Therefore, strengthening internal verification systems, improving service documentation standards, and optimizing coordination between service and administrative units are necessary to reduce the occurrence of pending claims and improve hospital management performance.